Half wave rectification of inorganic/organic heterojunction diode at the frequency of 1 kHz - Lee, Deuk-Hee; Park, Dong-Hoon; Kim, Sangsig; Lee, Sang Yeol (ELSEVIER SCIENCE SA, 2011)
An inorganic/organic vertical heterojunction diode has been demonstrated with p-type Poly(3,4-ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS) deposited by spin coating on n-type Ga-doped ZnO (GZO) thin films. Transparent conducting GZO thin films are deposited on glass substrate by rf-magnetron sputtering. Electrical properties of GZO thin films are investigated depending on the processing temperatures. The resistivity, mobility and carrier concentration of the GZO thin films deposited at processing temperatures of 500 degrees C are measured to be about 3.6 x 10(-4) Omega cm, 23.8 cm(2)/Vs and 7.1 x 10(20) cm(3), respectively. The root mean square surface roughness of the GZO thin films is calculated to be similar to 0.9 nm using atomic force microscopy. Current-voltage characteristics of the n-GZO/p-PEDOT:PSS heterojunction diode present rectifying operation. Half wave rectification is observed with the maximum output voltage of 1.85 Vat 1 kHz. Low turn-on voltage of about 1.3 V is obtained and the ideality factor of the n-GZO/p-PEDOT: PSS diode is derived to be about 1.8. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: ZINC-OXIDE FILMS; OPTICAL-PROPERTIES; ROOM-TEMPERATURE; TRANSPARENT; DEPOSITION